2016
DOI: 10.3390/su8100982
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Optimization of Renewables and Storages for Rural Electrification

Abstract: Abstract:The electricity access in Sub-Saharan African countries is below 10%; thus, introducing a microgrid for rural electrification can overcome the endemic lack of modern electricity access that hampers the provision of basic services such as education, healthcare, safety, economic and social growth for rural communities. This work studies different possible comparison methods considering variations such as land area required, location for the storage, efficiency, availability and reliability of energy res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
(10 reference statements)
0
12
0
Order By: Relevance
“…Both of these strategies make economic dispatch decisions; they choose the most economical way to serve the load at each time step. HOMER simulates hundreds or even thousands of all possible combinations of the energy system and then ranks the results according to the least-cost options that meet the load requirements [25][26][27].Many studies throughout the world have used HOMER software to investigate the optimal design of proposed HESs using LF or CC strategies. Halabi et al [28], Ansong et al [29], Sigarchian et al [30], Rezzouk and Mellit [31], and Madziga et al [32] used the LF strategy to analyze the performance of suggested HESs to find the optimal configurations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these strategies make economic dispatch decisions; they choose the most economical way to serve the load at each time step. HOMER simulates hundreds or even thousands of all possible combinations of the energy system and then ranks the results according to the least-cost options that meet the load requirements [25][26][27].Many studies throughout the world have used HOMER software to investigate the optimal design of proposed HESs using LF or CC strategies. Halabi et al [28], Ansong et al [29], Sigarchian et al [30], Rezzouk and Mellit [31], and Madziga et al [32] used the LF strategy to analyze the performance of suggested HESs to find the optimal configurations.…”
mentioning
confidence: 99%
“…Both of these strategies make economic dispatch decisions; they choose the most economical way to serve the load at each time step. HOMER simulates hundreds or even thousands of all possible combinations of the energy system and then ranks the results according to the least-cost options that meet the load requirements [25][26][27].…”
mentioning
confidence: 99%
“…Results have also been reported for hybrid renewable energy systems involving three primary energy technologies. Examples include PV-wind-hydro-battery systems [15]; PV, wind and storage integration on small islands [16]; wind-PV-battery systems [17]; wind-photovoltaic energy storage and transmission hybrid power systems [18]; grid-connected photovoltaic-wind-biomass power systems [19]; solar-diesel-battery systems [20]; solar-fuel cell-battery systems [21]; solar-wind-battery systems [22]; wind-solar-natural gas [23]; solar-wind-fuel cell systems [24]; solar-wind-diesel-battery systems [25]; and solar-wind-desalination systems [26]. For comparative purposes, it is noted that hybrid energy systems driven by fossil fuels have also been examined, such as fuel cell-gas turbine systems [27].…”
Section: Introductionmentioning
confidence: 99%
“…A current topic is the development of hybrid systems [25][26][27][28][29][30][31][32]; therefore, the addition of peripheral elements, such as auxiliary power units or backup sources intensifies the challenge of modeling highly coupled multi-physical systems. There are also complete studies concerning the design, improvement or modeling of converters for fuel cell applications (e.g., [33][34][35]).…”
Section: Introductionmentioning
confidence: 99%